An Analysis of Social Networking Sites: Privacy Policy and Features - Abuhassira, Mohammed M.O. (2012)
Social Networking Sites (SNSs) are at the heart of many people lives, and the majority of both students and adults who use them to share information, keeping contact with old friends and meeting new acquaintances. However, the increasing number of action on online services also gives a raised to privacy concerns and issues. Therefore, the main purpose of this study is investigate the two SNSs i.e. Facebook and Friendster in terms of privacy policy and features, users‟ preferences and needs as well as producing a guideline for good SNSs from users design perspective. In an attempt to achieve the objectives of this study, however, two different approaches were employed; first literature has reviewed for two SNSs for the comparative analysis, and secondly quantitative approach technique was used. Online questionnaire was designed and published on the web and the respondents were able to access and sent back respectively. The survey was limited only to one hundred respondents within the Universiti Utara Malaysia. Findings from this study reveal that there are significant differences and similarities between Facebook and Friendster privacy policy and features. However, Friendster has hidden users‟ identity information by default to only friends, while Facebook has made it public to everyone. Results from survey in this study indicate that most of the respondents disclose information including personal and private information with public and friends, nevertheless, many respondents prefer to share their personal and private information with friends. Although, majority of respondents are aware of privacy setting changes, while they have notable attitude toward privacy protection as well as trust. This study usher a new era towards knowledge of social networking sites and the result can be use to the body of literature on information system with emphasis on privacy policy setting and features.